A reduced and robust reaction mechanism for toluene and decalin oxidation with polycyclic aromatic hydrocarbon predictions. (1st January 2020) - Li, Guangze; Yang, Wenming; Tay, Kun Lin; Yu, Wenbin; Chen, Longfei
Highlights: A new reduced reaction mechanism for toluene and decalin oxidation was proposed. The current mechanism was comprehensively validated with experimental data. Negative temperature coefficient regime of decalin ignition delay time was analyzed. Sensitivity analysis was conducted for four typical polycyclic aromatic hydrocarbons. Abstract: In this work, a reduced toluene-decalin reaction mechanism containing 108 species and 566 reactions was proposed for computational fluid dynamics (CFD) simulations and polycyclic aromatic hydrocarbon (PAH) formation predictions in combustion engines. The present mechanism was validated with the available literature data including ignition delay time (IDT) determined in shock tubes and rapid compression machines (RCM), species mole fractions measured in premixed flames and jet stirred reactors (JSR), and laminar flame speeds. Moreover, a sensitivity analysis was performed on toluene and decalin flames to further investigate the main formation pathways of four representative PAHs: benzene (A1 ), naphthalene (A2 ), phenanthrene (A3 ) and pyrene (A4 ). In general, the simulation results exhibited a reasonable agreement with the experimental data. The negative temperature coefficient (NTC) behaviors of decalin IDTs were accurately reproduced by the proposed mechanism. The PAH species concentrations were also well captured for ethylene and benzene flames. The sensitivity analysis results indicated that the main formation reactions for PAHs have a strong link with ring structures. The decompositions of toluene and decalin primarily contributed to the formation of A1 . For toluene, A2 was formed by the reactions A1 - + C4 H3  = A2 and IC4 H5  + A1  = A2  + H2  + H, while for decalin, the self-combination reaction of C5 H5 became the main pathway. In addition, the reactions of the aromatic molecules and radicals significantly promoted the formation of A3 and A4 for both toluene and decalin.